Dampak Transformasi Sistem Pendidikan Pesantren terhadap Penanaman Jiwa Keikhlasan Santri - Ahmad Suradi (At-Ta'dib, 2018)
This article discusses that contemporary pesantren education, not only changes the socio-cultural base and knowledge of santri, but also affects Muslims as a whole. Therefore, major changes made by kyai to pesantren institutions today are not an alternative choice that is crossed the road, but is an accumulation of the values of life of pesantren whose history, without leaving the soul of sincerity or typical traditions. The impact of the transformation of pesantren on the inculcation of the spirit of sincerity in pesantren has shifted. This type of research is field research. That is using the object of research as a source of data acquisition or information. This study found that the impact of the transformation of pesantren on the inculcation of the soul of sincerity in pesantren has shifted. currently pesantren in bengkulu province began to shift in modern cultures are synonymous with luxury and consumptive. Pesantren in instilling Five Spirit (ruh) need to be open and flexible to the demands and developments of world, but still provide filter for its basic value do not fade (Islamic value). Pesantren does not only transform the outside (purpose, curriculum, method, management system and management of pesantren) but also need to wisely transform the depth as well (sincere values in pesantren).